Net force : threat point : a novel - Preisler, Jerome; Clancy, Tom, 1947-2013; Pieczenik, Steve R. (Hanover Square Press, 2021)
"The United States may seem safe from within but beyond its borders, a new enemy rises. An American ship has vanished. The president has tasked the new cyber-intelligence agency, Net Force, with finding out what happened to the vessel. But their investigation reveals a plan that could trigger a world war. Their only option is to strike first. Through the streets of New York, a secret city in Crimea and the depths of the South China Seas, Net Force must race to discover who is behind the attack...before it's too late."--Back cover.